Extending W2000 framework to design presentational aspects of web applications. - Ahmad@Sharif, Mohd. Nazir; Zakaria, Nor Hidayati (Penerbit UTM Press, 2003)
The Unified Modeling Language (UML) has been accepted as a de facto standard for modeling an artifact of the system. Recently, there are many initiatives that have been done on UML-based modeling system such as in real time systems, management information system, web based and hypermedia applications. This paper presents a UML profile for modeling presentational aspects of Web applications by using an extended of W2000 Design Framework that blends together the UML and Hypermedia Design Model (HDM). UML has been chosen because of its being a standard, its graphical and intuitive representations, and its extensibility for representing domain-specific notations. The HDM is a hypermedia model recognized as the ancestor of a family of several design models. This work is part of the using an extended W2000 framework for developing hypermedia for Web or generally, Web applications design. The approach has been demonstrated by designing the presentational aspect of e-marketing for the house developer enterprise. As a result, we have proposed the comprehensive enhanced framework by providing a presentational aspects of the system to the original framework. This framework is very useful for designing Web applications by utilizing the advantages of UML and HDM.